2022
DOI: 10.1002/ptr.7361
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin inhibits the stemness of anaplastic thyroid carcinoma cells by triggering autophagy‐lysosome mediated OCT4A degradation

Abstract: Capsaicin (CAP) is a well‐known anti‐cancer agent. Recently, we reported capsaicin‐induced apoptosis in anaplastic thyroid cancer (ATC) cells. It is well accepted that the generation of cancer stem cells (CSCs) is responsible for the dedifferentiation of ATC, the most lethal subtype of thyroid cancer with highly dedifferentiation status. Whether CAP inhibited the ATC growth through targeting CSCs needed further investigation. In the present study, CAP was found to induce autophagy in ATC cells through TRPV1 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Furthermore, capsaicin is involved in the autophagic degradation of OCT4A, a cell stemness regulator. The reduction of stemness can probably ameliorate ATC aggressiveness [ 108 ]. In a word, these agents have great pharmacological and economic benefits, and more translational researches and clinical trials are required in the future.…”
Section: Autophagy Is a Promising Target For Tc Treatmentsmentioning
confidence: 99%
“…Furthermore, capsaicin is involved in the autophagic degradation of OCT4A, a cell stemness regulator. The reduction of stemness can probably ameliorate ATC aggressiveness [ 108 ]. In a word, these agents have great pharmacological and economic benefits, and more translational researches and clinical trials are required in the future.…”
Section: Autophagy Is a Promising Target For Tc Treatmentsmentioning
confidence: 99%
“…In addition, as a natural alkaloid derived from Capsicum spp. [110], Capsaicin (trans-8-methyl-N-vanillyl-6-nonenamide, CAP) is a natural alkaloid [110], which inhibits the stemness of mesenchymal TC cells by activating autophagic lysosomal-mediated degradation of OCT4A [111]. The action of CAP on ATC helps us explore new ATC-targeting drugs [108,[112][113][114].…”
Section: The Role Of Inhibitors Substances and Autophagy In Thyroid-r...mentioning
confidence: 99%
“…Capsaicin is approved by the FDA for topical use in pain management of arthritis, diabetic neuropathy, and neuralgia and also to treat post-surgical neuropathic pain in cancer patients 32 . Numerous reports have shown that capsaicin induces cell cycle arrest and apoptosis in cancer cell lines 33 and autophagy in anaplastic thyroid carcinoma cells 34 . Interestingly, co-treatment of cancer cells with capsaicin and capsazepine (a TRPV1 antagonist) showed that cells still die by apoptosis 35 , suggesting that cytotoxicity was independent of TRPV1 activation, which was confirmed in an oral cancer model 36 .…”
Section: Introductionmentioning
confidence: 99%